Combined resistance and aerobic exercise intervention improves fitness, insulin resistance and quality of life in survivors of childhood haemopoietic stem cell transplantation with total body irradiation. Issue 12 (12th October 2020) - Davis, Nikki L.; Tolfrey, Keith; Jenney, Meriel; Elson, Ruth; Stewart, Claire; Moss, Andrew D.; Cornish, Jacqueline M.; Stevens, Michael C. G.; Crowne, Elizabeth C.
Abstract: Purpose: To investigate the effects of a supervised combined resistance and aerobic training programme on cardiorespiratory fitness, body composition, insulin resistance and quality of life (QoL) in survivors of childhood haematopoietic stem cell transplantation (HSCT) with total body irradiation (TBI). Participants: HSCT/TBI survivors ( n = 20; 8 females). Mean (range) for age at study and time since HSCT/TBI was 16.7 (10.9‐24.5) and 8.4 (2.3‐16.0) years, respectively. Methods: After a 6‐month run‐in, participants undertook supervised 45‐ to 60‐minute resistance and aerobic training twice weekly for 6 months, with a 6‐month follow‐up. The following assessments were made at 0, 6 (start of exercise programme), 12 (end of exercise programme) and 18 months: Body composition via dual energy X‐ray absorptiometry, homeostatic model assessment of insulin resistance (HOMA‐IR), cardiorespiratory fitness (treadmill‐based peak rate of oxygen uptake (VO2 peak) test), QoL questionnaires (36‐Item Short Form Health Survey (SF‐36) and Minneapolis‐Manchester Quality of Life Instrument (MMQL). Results: Results expressed as mean (standard deviation) or geometric mean (range). There were significant improvements in VO2 peak (35.7 (8.9) vs 41.7 (16.1) mL/min/kg, P = 0.05), fasted plasma insulin (16.56 (1.48‐72.8) vs 12.62 (1.04‐54.97) mIU/L, P = 0.03) and HOMA‐IR (3.65 (0.30‐17.26) vs 2.72 (0.22‐12.89), P = 0.02) after the exercise intervention. There were also significant improvements in the SF‐36 QoL general health domain (69.7 (14.3) vs 72.7 (16.0), P = 0.001) and the MMQL school domain (69.1 (25.2) vs (79.3 (21.6), P = 0.03) during the exercise intervention. No significant changes were observed in percentage body fat, fat mass or lean mass. Conclusion: The supervised 6‐month combined resistance and aerobic exercise programme significantly improved cardiorespiratory fitness, insulin resistance and QoL in childhood HSCT/TBI survivors, with no change in body composition, suggesting a metabolic training effect on muscle. These data support a role for targeted physical rehabilitation services in this group at high risk of diabetes and cardiovascular disease.